BICEP2/SPUD: searching for inflation with degree scale polarimetry from the South Pole - Nguyen, Hien Trong; Kovac, John; Adec, Peter; Aikin, Randol; Benton, Steve; Bock, Jamie; Brevik, Justus; Carlstrom, John; Dowell, Darren; Duband, Lionel; Golwala, Sunil; Halpern, Mark; et al. (Pasadena, CA : Jet Propulsion Laboratory, National Aeronautics and Space Administration, 2008, 2014)
BICEP2/SPUD is the new powerful upgrade of the existing BICEP1 experiment, a bolometric receiver to study the polarization of the cosmic microwave background radiation, which has been in operation at the South Pole since January 2006. BICEP2 will provide an improvement up to 10 times mapping speed at 150 GHz compared to BICEP1, using the same BICEP telescope mount. SPUD, a series of compact, mechanically-cooled receivers deployed on the DASI mount at the Pole, will provide similar mapping speed in to BICEP2 in three bands, 100, 150, and 220 GHz. The new system will use large TES focal plane arrays to provide unprecedented sensitivity and excellent control of foreground contamination. NASA/JPL